Origenes y evolución de la crónica taurina - Forneas Fernández, María Celia (Estudios sobre el Mensaje Periodístico, 2007)
This article essentially comes from a lecture offered on July 13rd, 2006 at Complutense University’s Summer Courses, in San Lorenzo de El Escorial. That is “Two hours after five o´clock in the afternoon“…, managed by the professor Juan Gómez Castañeda. The subject agreed was “Origin and development of bullfighting chronicle”. Naturally, it was also necessary to clarify concepts like “review”, “chronicle” and “critic”.
Keywords: Bullfighting chronicle; Bullfighting critic; Bullfighting review